提高加州鲈鱼苗成活率的饲料添加剂 (2017)
本发明涉及水产动物养殖技术领域，尤其涉及种提高加州鲈鱼种成活率的饲料添加剂，由下列质量百分比的原料组成：β-1，3葡聚糖25～35％、低分子壳寡糖15～25％、维生素C10～20％、凝结芽孢杆菌12～17％、乳酸杆菌10～15％、柠檬酸6～10％、苦参5～8％和蛋氨酸锌3～6％，且各原料的质量和为100％。本发明的效果包括：(1)在加州鲈饲料中作为饲料添加剂使用，添加量仅为0.1～0.3％(质量百分数，下同)；(2)能明显增强加州鲈的免疫力和抗病力，提高成活率；(3)所用的原料来源稳定、价格低廉，生产工艺简单。 The invention relates to the technical field of aquaculture, in particular to a feed additive for increasing the survival rate of micropterus salmoides fry. The feed additive is composed of the following raw materials by mass percent: 25-35% of beta-1, 3-glucan, 15-25% of low molecular chitosan oligosaccharide, 10-20% of vitamin C, 12-17% of bacillus coagulans, 10-15% of lactobacillus, 6-10% of citric acid, 5-8% of sophora flavescens and 3-6% of zinc methionine; the total mass of the raw materials is 100%. The feed additive for increasing the survival rate of micropterus salmoides fry has the following effects: (1) the dose of the feed additive in micropterus salmoides feed is only 0.1-0.3% (by mass, the same below); (2) the immunity and disease resistanc